The Relationship Between Online Application Usage Intensity and Student Learning Motivation in the Digital Era - Nabila, Nayumi Warta; Ramadhani, Khalila Humairo; Sari, Bq. Roswin Tiarti; Gunawan, Gunawan (Indonesian Publication Center, 2025)
The integration of digital technology in modern education offers flexibility while presenting technical challenges that influence student engagement. This study aims to analyze the intensity of online application usage, student learning motivation, and the correlation between these two variables among students at the University of Mataram. A quantitative approach with a correlational survey design was employed, collecting data from 64 students via Likert-scale questionnaires in November 2025. Data were analyzed using descriptive statistics and Pearson correlation. The findings indicate that the intensity of online application usage falls within the moderate category, with Google Meet and Zoom being the most dominant platforms. Similarly, student learning motivation is categorized as fair, influenced by ease of use and the quality of academic interaction. Pearson correlation analysis revealed a significant positive relationship between online application usage intensity and student learning motivation (r = 0.41; p < 0.05), representing a moderate correlation strength. These results underscore that meaningful and intensive use of online applications has the potential to enhance student motivation, although technical and pedagogical factors remain critical in determining the overall effectiveness of digital learning.